Methylobacterium sp. 2A Is a Plant Growth-Promoting Rhizobacteria That Has the Potential to Improve Potato Crop Yield Under Adverse Conditions - Grossi, Cecilia Eugenia María; Fantino, Elisa; Serral, Federico; Zawoznik, Myriam Sara; Fernandez Do Porto, Darío Augusto; Ulloa, Rita María (Frontiers in Plant Science, 2020)
A Gram-negative pink-pigmented bacillus (named 2A) was isolated from Solanum tuberosum L. cv. Desirée plants that were strikingly more developed, presented increased root hair density, and higher biomass than other potato lines of the same age. The 16S ribosomal DNA sequence, used for comparative gene sequence analysis, indicated that strain 2A belongs to the genus Methylobacterium. Nucleotide identity between Methylobacterium sp. 2A sequenced genome and the rest of the species that belong to the genus suggested that this species has not been described so far. In vitro, potato plants inoculated with Methylobacterium sp. 2A had a better performance when grown under 50 mM NaCl or when infected with Phytophthora infestans. We inoculated Methylobacterium sp. 2A in Arabidopsis thaliana roots and exposed these plants to salt stress (75 mM NaCl). Methylobacterium sp. 2A-inoculated plants, grown in control or salt stress conditions, displayed a higher density of lateral roots (p<0.05) compared to non-inoculated plants. Moreover, under salt stress, they presented a higher number of leaves and larger rosette diameter. In dual confrontation assays, Methylobacterium sp. 2A displayed biocontrol activity against P. infestans, Botrytis cinerea, and Fusarium graminearum, but not against Rhizoctonia solani, and Pythium dissotocum. In addition, we observed that Methylobacterium sp. 2A diminished the size of necrotic lesions and reduced chlorosis when greenhouse potato plants were infected with P. infestans. Methylobacterium sp. 2A produces indole acetic acid, solubilizes mineral phosphate and is able to grow in a N2 free medium. Whole-genome sequencing revealed metabolic pathways associated with its plant growth promoter capacity. Our results suggest that Methylobacterium sp. 2A is a plant growth-promoting rhizobacteria (PGPR) that can alleviate salt stress, and restricts P. infestans infection in potato plants, emerging as a potential strategy to improve crop management.